A role for the MEGF6 gene in predisposition to osteoporosis - Teerlink, Craig C. (Ann Hum Genet, 2020)
Osteoporosis is a common skeletal disorder characterized by deterioration of bone tissue in later life. The set of genetic factors contributing to osteoporosis is not completely specified. Whole exome sequencing was performed on affected-relative-pairs, approximately cousins, from 10 high-risk osteoporosis pedigrees to identify rare, highly penetrant candidate predisposition variants. Variants were filtered on population frequency and concordance between pairs of cousins. We identified 3 candidate variants that were tested for segregation in 74 additional relatives of the index carriers. A rare variant in MEGF6 (rs755467862) showed the strongest evidence of segregation, with 6 affected pedigree members carrying the variant (RVsharing probability=0.0011). Functional impact of the MEGF6 variant was analyzed via in-silico prediction of protein folding disruption using I-Tasser software that predicted substantial protein folding differences between wild type and variant MEGF6 proteins. Predicted protein folding showed that the variant (Cys200Tyr) may disrupt a disulfide bond between residues 187 and 200 in the second EGF-like calcium-binding domain of MEGF6, likely eliminating a calcium binding site. Furthermore, functional analyses in zebrafish demonstrate that the paralogous genes megf6a and megf6b contribute in a redundant fashion to cartilage and bone formation. Segregation analyses, in-silico protein structure modeling, and functional assays support a role for MEGF6 in predisposition to osteoporosis.